Preventive percutaneous coronary intervention versus optimal medical therapy for vulnerable plaque: a meta-analysis - Yating Chen; Xiaochen Liu; Yuyao Qiu; Qian Guo; Feiyu Zhang; Shaoping Nie; Hongtao Liu; Deyong Long; Xiao Wang (BMC Cardiovascular Disorders)
Abstract Background The effectiveness and safety of preventive percutaneous coronary intervention (PCI) on non-flow limiting vulnerable coronary plaque remain uncertain. Objective The aim of this meta-analysis was to evaluate the impact of preventive PCI plus optimal medical therapy (OMT) in non-flow limiting vulnerable plaque on clinical outcomes compared with OMT alone. Method We searched PubMed, Embase, Web of Science (WOS), and the Cochrane from inception date to October 2024 for relevant studies which compared OMT and PCI plus OMT for non-flow limiting vulnerable plaques. Of the included studies, vulnerable plaques were defined as angiographically intermediate and non-flow limiting plaques with one or more of the following characteristics such as thin-cap fibroatheromas (TCFA), high lipid content, large plaque burden or small luminal area, although specific criteria differed among studies. The primary outcome was major adverse cardiac event (MACE). Pooled risk ratios (RR) were calculated using random effects models and heterogeneity was evaluated with the I2 statistic. Result We included 4 randomized clinical trials with 1,843 participants. The follow-up duration ranged from 6 to 25 months. Patients in PCI group had similar incidence of MACE compared with OMT group (RR = 0.38; 95% CI 0.10 to 1.45; P = 0.16). For individual components of MACE, there were no statistical differences in the incidence of all-cause death, myocardial infarction (RR = 0.55; 95% CI 0.05 to 6.51; P = 0.64; RR = 0.81; 95% CI 0.12 to 5.19; P = 0.82). However, compared with OMT group, PCI group experienced a reduction of clinically-driven revascularization and hospitalization for unstable or progressive angina (RR = 0.11; 95% CI: 0.03–0.40; P < 0.001; RR = 0.16; 95% CI: 0.05–0.56; P = 0.004). Conclusion In patients with non-flow limiting vulnerable plaques, preventive PCI plus OMT showed a similar incidence of MACE but a reduction in the incidence of clinically-driven revascularization and hospitalizations for unstable or progressive angina, compared with OMT alone.